Midblock Signalled Pedestrian Crossing - Alternative Controller Algorithms (Malaysian Journal of Civil Engineering, 2018)
Observation at midblock signalled pedestrian crossings in Malaysia showed thatviolation of the red signal aspect by both the motorists and pedestrians is close to70 %. Motorists may travel on the red signal aspect when there is no pedestrianon the crossing. Pedestrians are also observed to cross in vehicle gaps at thecrossings during the right of way to vehicles. Such behaviour is dangerousespecially at a system where the traffic movements rely on the signal aspectsshown to them. Four alternative algorithms were designed in order to enhancethe operation and safety of users at the midblock signalled pedestrian crossings inMalaysia. The objectives are to increase pedestrian safety and drivers compliancewith the signal. The developed strategies required detectors to register the vehicleand pedestrian demands. Algorithms were designed to compute the appropriatetime to start and terminate the vehicle and pedestrian precedence. The appliedcomputation aimed to limit vehicle delay and to ensure that vehicle saturationflow does not exceed 85 % of the road capacity. Apart from the vehicle demands,the developed strategies also attempt to emphasis on the requirement and limitsof pedestrian behaviour. Four measures of performance are compared andevaluated. These measures are the percentage of vehicles crossing on the redman, pedestrian mean delay, mean cycle times and vehicle mean delay. Themeasures of performance of all algorithms are evaluated using a fully calibratedand validated simulation program. All of the new strategies increase thepedestrian compliance and balance. This indicates that the present system doesnot respond satisfactorily to the gaps in vehicle flow and may contribute to theusers disrespect of the system.